Urgent Surgery for Giant Pancreatic Neuroendocrine Tumor: A Case Report - Teresa, Gimenez Maurel; Alejandra, Utrilla Fornals; Leyre, Serrablo Casaña; Angel, Trigo Gómez Miguel; Alejandro, Serrablo Requejo (Archives of Clinical and Medical Case Reports, 2020)
Pancreatic neuroendocrine neoplasms (P-NENs) are a heterogeneus group of tumors with a low frequency of occurrence (<1/100.000 patients per year). Their incidence has been increasing in the past decades mainly due to incidental discovery of asymptomatic lesions. Approximately, 60% of patients present metastases during the diagnostic process and the liver is the most frequent location where the methastases present themselves. Even though in 2010, the World Health Organization (WHO) presented the most accepted classification so far, that divided P-NENs into well-differentiated neuroendocrine tumors (NETs) and less well-differentiated neuroendocrine carcinomas (NECs), a universally standardized classification is still needed. Imaging tests such as CT or MRI are frequently used for diagnosis but Octreoscan and further complex techniques including preoperative biopsy are also needed for a successful diagnosis. Surgery is the only possible curative treatment, however added adyuvant chemoterapy is considered to improve survival rates. We present the case of a 56-year-old patient who suffered from P-NEN and underwent an aggressive surgery with curative intent. We consider the interest given due to the large size of the tumor, its liver metastases, and the correct surgical and oncological results obtained.